The Effects of Intermittent Hypoxic–Hyperoxic Exposures on Lipid Profile and Inflammation in Patients With Metabolic Syndrome - Afina, A. Bestavashvili; Oleg, S. Glazachev; Alexander, A. Bestavashvili; Ines, Dhif; Alexander Yu, Suvorov; Nikita, V. Vorontsov; Denis, S. Tuter; Daria, G. Gognieva; Zhang, Yong; Chavdar, S. Pavlov; Dmitriy, V. Glushenkov; Elena, A. Sirkina; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background Metabolic syndrome patients tend to suffer from comorbidities, and are often simultaneously affected by obesity, dysglycemia, hypertension, and dislipidemia. This syndrome can be reversed if timely diagnosed and treated with a combination of risk factors-reducing lifestyle changes and a tailored pharmacological plan. Interval hypoxic-hyperoxic training (IHHT) has been shown as effective at reducing cardiovascular risk factors in such patients even in absence of exercise. However, IHHT influence on lipid profile and inflammation in this clinical population remains relatively unknown. Methods A prospective, single-center, randomized controlled trial was conducted on 65 (33 male) metabolic syndrome patients aged 29-74 years, who were randomly allocated to IHHT or control (sham) experimental groups. The IHHT group completed a 3-week, 5 days/week intermittent exposure to hypoxia and hyperoxia. The control (sham) group followed the same protocol but were breathing room air instead. The primary endpoints were the Lipid profile (concentrations of total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides (TG)) and the inflammatory factors such as high-sensitivity C-reactive protein (hs-CRP), galectin-3, heat shock proteins (Hsp70). The secondary endpoints included alanine aminotransferase (ALT), aspartate aminotransferase (AST), N-terminal pro-hormone of brain natriuretic peptide level (NTproBNP), transforming growth factor beta-1 (TGF-beta1), heart-type fatty acid-binding protein (H-FABP), and nitric oxide synthase 2 (NOS2). Results: There were no differences between groups but the different baseline values have affected these results. The IHHT group demonstrated pre-post decrease in total cholesterol (p=0.001), LDL (p=0.001), TG levels (p=0.001). We have also found a decrease in CRP-hs (p=0.015) and Hsp70 (p=0.006) in IHHT-group after intervention, and a significant decrease in pre-post (delta) differences of NTproBNP (p<0.0001) in IHHT group compared to the control group. Also, the patients of the IHHT group showed a statistically significant decrease in pre-post differences of ALT and AST levels in comparison with the control group (p=0.001). No significant IHHT complications or serious adverse events were observed. Conclusions: IHHT appears to improve lipid profile and anti-inflammatory status. It is a safe, well-tolerated procedure, and could be recommended as an auxiliary treatment in patients suffering from metabolic syndrome, however, our results were limited by the baseline group differences.